Consistent or balanced? On the dynamics of voluntary contributions - Carlo Gallier; Christiane Reif; Daniel Römer (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2015)
We investigate the dynamic effects of a charitable lottery and an income tax on donations. The analysis is based on a two-round dictator game with the subject's charity of choice as recipient and additional incentives in the first round only. The immediate effect of a charitable lottery leads to higher contributions and we cannot find substantial crowding out of voluntary contributions in the presence of an income tax. These economic interventions weakly spill-over to the subsequent donation decisions without additional incentives. Our results suggest the presence of consistency seeking behaviour. This is especially true for a subgroup of participants with a rule-based mind-set and our research shows the importance of the subjects' moral framework in the context of dynamic pro-social behaviour.
Keywords: C91; D03; D64; H41; 330; Experiment; Charitable Giving; Lottery; Tax; Modified Dictator Game; Moral Balancing